A retrospective study of intraductal papillary neoplasia of the pancreas (IPMN) under surveillance. (March 2022) - Johansson, Katarina; Kaprio, Tuomas; Nieminen, Heini; Lehtimäki, Tiina E.; Lantto, Eila; Haglund, Caj; Seppänen, Hanna
Background and objective: The growing number of identified intraductal papillary mucinous neoplasm (IPMN) patients places greater pressure on healthcare systems. Only a minority of patients have IPMN-related symptoms. Thus, more precise surveillance is required. Methods: In this retrospective single-center cross-sectional study, patients with an active diagnosis of branch duct IPMN (BD-IPMN) and >6 months of surveillance were classified as follows: presence/absence of worrisome features (WF) or high-risk stigmata (HRS), newly developed WF/HRS, under/over 15 mm cyst, growing/not growing <15 mm cyst, and elevated serum carbohydrate antigen 19-9 (CA 19-9). Results: In all, 377 patients with BD-IPMN were followed for a median of 5.4 years, 28% with WF at diagnosis, and 14% who developed WF/HRS during surveillance. Half had a <15 mm primary cyst, 40% of which did not grow during surveillance. CA 19-9 was elevated in 12%. None of the patients with normal CA 19-9 levels developed cancer or high-grade dysplasia (HGD). Conclusions: No carcinomas or HGDs appeared with normal CA 19-9 levels. Patients with <15 mm cysts that do not grow and have no WF/HRS could undergo imaging less frequently.